Into the wild: How exposure to wild or domesticated fungi shapes immune responses in mice - Chen, Ying-Han; Cadwell, Ken (PLoS pathogens, 2022)
Human subject studies have linked disruption of the intestinal bacterial community to a variety of disease conditions, and experimental models have helped us interpret these findings by elucidating mechanisms by which bacteria evoke pro- or anti-inflammatory responses through host cells and receptors. [...]there is growing evidence that the limited microbial exposure experienced by laboratory mice kept in ultra-hygienic specific pathogen-free (SPF) facilities leads to a less mature immune system when compared with free-living mammals such as humans. [...]fungi in the natural environment contribute to the composition of circulating immune cells. [...]systemic IL-17A induced by mucosal fungi acts on neurons to regulate social behavior in mice, demonstrating how the gut mycobiota can contribute to the gut–brain axis [27].